ЖАСЛАРДЫ КӘСИПКЕ АДАПТАЦИЯ ҚЫЛЫЎДА ҮЛГИ ОҚЫЎ БАҒДАРЛАМАЛАРЫНА ҚОЙЫЛАТУҒЫН ТАЛАПЛАР - Қыдырниязов, Қ.Ж. (FAN va JAMIYAT, 2021)
The author discusses the following issues: career guidance, career choice, comprehensive development of young people in the process of vocational adaptation, education, systematic and quality education, avoidance of negative positions, strengthening education with legislation, political awareness, creativity approach, integrated education, the role of curricula and model curricula in the implementation of strategic plans of the state, the role of the system of continuing education in the training of qualified personnel and improving the content of education.